Distribution of the gas temperature in streamer discharge in air - Bolotov, O.V.; Golota, V.I.; Gurtovoi, S.D. (Вопросы атомной науки и техники, 2014)
The temperature of nitrogen molecules in streamer discharge in point-to-plane electrode system was determined by using optical emission spectroscopy. The emission spectra of streamer discharge in air, in a wavelengths range 300…400 nm, were studied. The electronic-vibrational-rotational structure of (0-0) – band emission spectrum of N2+ nitrogen system (C3Πu-B3Πg transitions) was analyzed for different points along streamer propagation in discharge gap. The gas temperature was calculated on the basis of measurements of relative intensities in the rotational structure of the spectra. It was shown that gas temperature in the discharge gap varies in the range of 380…730 K. It was noted that for different discharge conditions the gas temperature in vicinity of the anode and cathode area is higher than in the central part of the discharge gap.